Changes in Rice Grain Quality of Indica and Japonica Type Varieties Released in China from 2000 to 2014 - Feng, Fan; Li, Yajun; Qin, Xiaoliang; Liao, Yuncheng; Siddique, Kadambot H. M. (Frontiers in Plant Science, 2017)
China is the first country to use heterosis successfully for commercial rice production. This study compared the main quality characteristics (head rice rate, chalky rice rate, chalkiness degree, gel consistency, amylose content and length-to-width ratio) of 635 rice varieties (not including upland and glutinous rice) released from 2000–2014 to establish the quality status and offer suggestions for future rice breeding for grain quality in China. In the past 15 years, grain quality in japonica rice and indica hybrid rice has improved. In japonica rice, inbred varieties have increased head rice rates and decreased chalkiness degree over time, while hybrid rice varieties have decreased chalky rice rates and chalkiness degree. In indica hybrid rice, the chalkiness degree and amylose contents have decreased and gel consistency has increased. Improvements in grain quality in indica inbred rice have been limited, with some increases in head rice rate and decreases in chalky rice rate and amylose content. From 2010–2014, the percentage of indica varieties meeting the Grade III national standard of rice quality for different quality traits was low, especially for chalky rice rate and chalkiness degree. Japonica varieties have more superior grain quality than indica rice in terms of higher head rice rates and gel consistency, lower chalky rice rates and chalkiness degree, and lower amylose contents, which may explain why the Chinese prefer japonica rice. The japonica rice varieties, both hybrid and inbred, had similar grain qualities, but this varied in indica rice with the hybrid varieties having higher grain quality than inbred varieties due to significantly better head rice rates and lower chalkiness degree. For better quality rice in future, the chalky rice rate and chalkiness degree should be improved in japonica rice along with most of the quality traits in indica rice.